Phytochemical Screening and FTIR Characterisation of Ultrasonic Assisted Methanolic Extract of Chlorococcum humicola: Evaluation of its Antioxidant and Anti-inflammatory Activities - Vanitha, E.; Dhandayuthapani, K. (Asian Journal of Chemistry, 2026)
This study investigates the phytochemical composition and evaluates the antioxidant and anti-inflammatory potential of an ultrasonic-assisted methanolic extract (UAME) obtained from the double mutant Chlorococcum humicola MCH4 cultivated in ultrasonically pretreated municipal wastewater (UPMWW). Qualitative phytochemical screening revealed a broader spectrum of bioactive compounds in the mutant strain compared with the wild strain C. humicola KMS2, in which glycosides, tannins and phytosterols were absent. Quantitative analysis showed high total phenolic content (59.47 ± 0.09 mg GAE/g DW), total flavonoid content (62.47 ± 0.12 mg QE/g DW) and total carotenoids (4.11 mg/g), confirming the enriched phytochemical profile of C. humicola MCH4. Based on these results, the UAME of the mutant strain was selected for further biological evaluation. The extract exhibited notable radical-scavenging activity in DPPH and ABTS assays with IC50 values of approximately 50 µg/mL. In vitro anti-inflammatory assays demonstrated concentration-dependent inhibition of albumin denaturation (IC50 ≈ 59.4 µg/mL), proteinase activity (IC50 ≈ 57.0 µg/mL) and lipoxygenase activity (IC50 ≈ 55.2 µg/mL), indicating promising preliminary activity. FTIR analysis confirmed the presence of hydroxyl, carbonyl and aliphatic functional groups associated with phenolics, proteins, lipids, carotenoids and carbohydrates. The results indicate that the double mutant C. humicola MCH4 cultivated in UPMWW serves as a sustainable and promising source of bioactive compounds with potential applications in pharmaceutical, nutraceutical and cosmeceutical fields.